Conception of a flexible integrator and lean model for integrated management systems - Rebelo, Manuel (2013)
Management systems standards (MSSs) have developed in an unprecedented manner in the last few years. These MSS cover a wide array of different disciplines, aims and activities of organisations. Also, organisations are populated with an enormous diversity of independent management systems (MSs). An integrated management system (IMS) tends to integrate some or all components of the business. Maximising their integration in one coherent and efficient MS is increasingly a strategic priority and constitutes an opportunity for businesses to be more competitive and consequently, promote its sustainable success. Those organisations that are quicker and more efficient in their integration and continuous improvement will have a competitive advantage in obtaining sustainable value in our global and competitive business world. Several scholars have proposed various theoretical approaches regarding the integration of management sub-systems, leading to the conclusion that there is no common practice for all organisations as they encompass different characteristics. One other author shows that several tangible and intangible gains for organisations, as well as to their internal and external stakeholders, are achieved with the integration of the individual standardised MSs. The purpose of this work was to conceive a model, Flexible, Integrator and Lean for IMSs, according to ISO 9001 for quality; ISO 14001 for environment and OHSAS 18001 for occupational health and safety (IMS–QES), that can be adapted and progressively assimilate other MSs, such as, SA 8000/ISO 26000 for social accountability, ISO 31000 for risk management and ISO/IEC 27001 for information security management, among others. The IMS–QES model was designed in the real environment of an industrial Portuguese small and medium enterprise, that over the years has been adopting, gradually, in whole or in part, individual MSSs. The developed model is based on a preliminary investigation conducted through a questionnaire. The strategy and research methods have taken into consideration the case study. Among the main findings of the survey we highlight: the creation of added value for the business through the elimination of several organisational wastes; the integrated management of the sustainability components; the elimination of conflicts between independent MS; dialogue with the main stakeholders and commitment to their ongoing satisfaction and increased contribution to the company’s competitiveness; and greater valorisation and motivation of employees as a result of the expansion of their skill base, actions and responsibilities, with their consequent empowerment. A set of key performance indicators (KPIs) constitute the support, in a perspective of business excellence, to the follow up of the organisation’s progress towards the vision and achievement of the defined objectives in the context of each component of the IMS model. The conceived model had many phases and the one presented in this work is the last required for the integration of quality, environment, safety and others individual standardised MSs. Globally, the investigation results, by themselves, justified and prioritised the conception of an IMS–QES model, to be implemented at the company where the investigation was conducted, but also a generic model of an IMS, which may be more flexible, integrator and lean as possible, potentiating the efficiency, added value both in the present and, fundamentally, for future.